Pratiques alimentaires des mères et malnutrition infantile dans le district de santé de Pitoa : Etude cas-témoin - Benjamin Azike Chukuwchindun; Andre Pascal Goura; Landry Bitaa Beyala; Anthony Njimbia Chebe; Andre Izacar Gael Bita; Joliette Azakoh Nguefack; Jerome Ateudjieu (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
Background: Malnutrition is a major public health thread in Africa and Cameroon as well. A study of mothers’ feeding practices and child malnutrition can contribute to identify and optimise interventions to control malnutrition. Methods: This was an analytical case/control study with a simple random sampling.Data sources were a literature review to estimate the prevalence of referred malnutrition of children, a community detection of cases and controls. A total of 386 children were included in the study. Results: The prevalence of referred infant malnutrition was 47.89% (95% CI [45.58, 50.2]). The most affected age group was children aged between 6 to 29 months. Inappropriate feeding practices significantly increased the risk of malnutrition in children with OR = 3.44 [2.05; 5.76] (P˂0.05). After adjustment by the confounding factors we obtained an adjusted OR = 3.19 [2.08; 6.35] (P = 0.0007). The most common inappropriate feeding practices were: food taboos, non-fortified porridge, early or late introduction of supplementary foods. Conclusion: The prevalence of malnutrition remains very high in the health district of Pitoa. Poor feeding practices significantly increase the risk of malnutrition. Efficient interventions would include nutritional education and popularization of rich local foods.